2022
DOI: 10.3390/horticulturae8070653
|View full text |Cite
|
Sign up to set email alerts
|

Response of Common Ice Plant (Mesembryanthemum crystallinum L.) to Photoperiod/Daily Light Integral in Vertical Hydroponic Production

Abstract: Common ice plant (Mesembryanthemum crystallinum L.) is a novel edible plant with a succulent and savory flavor emerging as new crop for greenhouse and plant factory growers. Currently very limited information is available on the response of ice plant to photoperiod and to daily light integral (DLI). The objective of this study was to determine the impact of photoperiod/DLI on the growth of ice plant for indoor vertical production. Four-week old seedlings of ice plant were transplanted into vertical hydroponic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Additionally, CL had a detrimental impact on the rate of photosynthesis in leaves as well as the total dry weight of tomato plants 56 . It was also reported that CL has a negative impact on the fresh weight and dry weight of common ice plant 48 . Hence, the effect of photoperiod varies according to the type of crop as well as their cultivars (Supplementary Table 1 ).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, CL had a detrimental impact on the rate of photosynthesis in leaves as well as the total dry weight of tomato plants 56 . It was also reported that CL has a negative impact on the fresh weight and dry weight of common ice plant 48 . Hence, the effect of photoperiod varies according to the type of crop as well as their cultivars (Supplementary Table 1 ).…”
Section: Introductionmentioning
confidence: 96%
“…Because of the higher energy requirement, light intensities greater than 300 are generally not recommended 46 . While adding the extra photons by increasing PPFD has diminishing marginal gains, increasing photoperiod is another strategy to augment DLI and gross photosynthesis 17 , 47 , 48 .…”
Section: Introductionmentioning
confidence: 99%
“…Other reports have also demonstrated the positive effects of red light on plant growth for leafy vegetables such as lettuce and perilla [24][25][26]. Though there was a significant difference in the leaf area of the plants due to the light spectrum [27], the results were not conclusive for the daily light integral. The scattering plots found low correlation between the shoot weight, leaf area and leaf width and the photoperiod DLI.…”
Section: Discussionmentioning
confidence: 84%
“…While no differences in nitrate contents were observed among the light treatment receipts under 18 h DLI, it was seen that a light spectrum with a higher proportion of blue/red spectra leads to a higher nitrate content, as observed for light receipts 3 and 4 under 21 h DLI. The increase in the uptake of nitrate due to the photoperiod also positively affect the physical and morphological parameters such as the shoot weight, leaf area and leaf width [27].…”
Section: Discussionmentioning
confidence: 99%